Effectiveness of Thermotherapy in Reducing Pain in Patients with Acute Coronary Syndrome: A Quasi-Experimental Study - Gusmarta, Gusmarta; Nurhusna, Nurhusna; Oktarina, Yosi (STIKep PPNI Jawa Barat, 2025)
Background: Chest pain is the most common and distressing symptom experienced by patients with Acute Coronary Syndrome (ACS), often requiring rapid and effective management. While pharmacological therapies are standard, integrating non-pharmacological interventions such as thermotherapy may enhance pain control and patient comfort. Objective: This study aimed to evaluate the effectiveness of thermotherapy in reducing pain levels among patients with ACS. Methods: A quasi-experimental design was employed, involving 36 patients diagnosed with ACS at a hospital in Indonesia. Participants were divided equally into an intervention group (n = 18), who received thermotherapy in addition to standard care, and a control group (n = 18), who received standard care alone. Pain intensity was measured using the Numerical Rating Scale (NRS) before and after the intervention. Data were analysed using paired t-tests to compare pre- and post-intervention pain levels within each group, and independent t-tests to assess differences between groups. Results: The intervention group showed a statistically significant reduction in pain levels after receiving thermotherapy (p < 0.001). In contrast, the control group showed no significant change in pain levels (p = 0.088). Between-group analysis using an independent t-test revealed a significant difference in post-intervention pain scores (p < 0.001), indicating the effectiveness of thermotherapy. Conclusion: Thermotherapy is effective in reducing chest pain in patients with ACS and can be considered a complementary nursing intervention alongside standard care.